EFFECTIVENESS OF SKIN TRACTION ON PREOPERATIVE PAIN SCALE IN INTERTROCHANTERFRACTURE PATIENTS - Rahmasari, Ikrima; Widiastuti, Agung; Buyu Prakoso, Adi; Budiati, Dhiani (LPPM Universitas Duta Bangsa Surakarta, 2023)
Fracture is a condition where the continuity of bone tissue is broken. Intertrochanter fractures are fractures that occur in the pelvic bones with a transverse line from the greater trochanter to the lesser trochanter. Broken bones are a potential or real threat to a person's integrity, so they experience physiological and psychological disorders that can cause reactions in the form of pain. Traumatic pain due to bone fractures that damage healthy tissue. The first treatment is to observe whether there are other accompanying injuries, after that skin traction is applied which is considered effective before performing surgery to reduce pain. Objective: to determine the reduction in pain scale in intertrochanteric fracture patients after skin traction was applied. The method in this research uses a pre-experimental design with a one group pretest-posttest design. Data collection techniques used questionnaire sheets and the Numeric Rating Scale (NRS) pain scale. Data analysis used paired T test. The results showed that the intensity of pain before and after being given skin traction had decreased. The conclusion in the study was that the installation of skin traction before surgery could reduce the pain scale in intertrochanter fracture patients.